Foreign Investment and Labor Force Selected Arab Countries(Egypt, Tunisia, Saudi Arabia and Qatar) - سلوم, تاميم محمد; جواد, سجى فاضل (Journal of Economics and Administrative Sciences, 2011)
The world has witnessed in recent years a major development in the movement of investment, especially Foreign Direct Investment has got the developing countries, including Arab states share a small insignificant sometimes, despite the paucity of these flows, they have influenced, directly or indirectly in the labor force, and the provision of employment opportunities or Strengthening unemployment, and their impact in both cases depends on the availability of the determinants to attract foreign investment in host countries, and the extent of indulgence Governments of those countries with foreign investors through investment laws enacted by that may be imposed on foreign investors run a certain percentage of local workers.